John - Michaels, J. Ramsey (Grand Rapids : Baker Books, 2011)
A section-by-section commentary on the New Testament, written by scholars for pastors, teachers, and students of the Bible.
39 The Impending Departure I (John 13:36-14:31)
"Previously published jointly in 1995, in the United States by Hendrickson Publishers, and in the United Kingdom by the Paternoster Press."--T.p. verso.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Bible